Framing an EU Level Regularization Mechanism: Mission Impossible?. (8th March 2013) - Bilgic, Ali
Abstract: European Union Member States have so far tackled the problem of irregular migration in Europe by adopting common policies which aim to prevent irregular arrivals on the EU borders. In their EU‐level policies, they have neglected regularization as an alternative EU‐level policy addressing irregular migration. This represents a contrast to regularizations which are performed by many EU Member States. However, the EU Commission has gradually adopted a more positive stance about regularization. This article will discuss the principles of an EU‐level regularization scheme through the analysis of the Commission's ideas on the issue. It will be argued that, rather than adopting a common policy, the flexible set of measures, which guide Member States in formulating regularization mechanism for protection/humanitarian reasons, can be formulated at the EU level.